The social work experience : an introduction to social work and social welfare - Suppes, Mary Ann.; Wells, Carolyn Cressy (Boston, Mass. McGraw-Hill, 2000)
Created to introduce students to social work and its relationship to social welfare policy, this text offers a historical and practical overview of the profession. In each chapter, the authors integrate policy coverage with social work practice, values and ethics and social justice.
Includes bibliographical references and index.
Keywords: Social service -- United States; Social service -- Vocational guidance -- United States